Peningkatan Kapasitas Pengelola Homestay melalui Pelatihan Manajemen berbasis Kearifan Lokal Desa Wisata - Fitriana, Rina; Putri, Ni Made Dwiyana Rasuma; Harwindito, Baskoro; Noviadi, Andy; Maryetti, Maryetti (Penerbit Goodwood, 2025)
Purpose: This community service activity aims to improve the capacity of homestay managers in Leuwimalang Tourism Village, Bogor Regency, through local wisdom-based management training. This effort aims to strengthen the competitiveness of the tourism village while ensuring the sustainability of community-based tourism. Methodology/approach: The program was implemented using a participatory approach through socialization, homestay management training, practical mentoring, and evaluation. The training materials emphasized service management, marketing, simple financial management, and the integration of local wisdom values. Results/findings: This activity resulted in increased knowledge and skills of homestay managers in aspects of service, financial record keeping, and local wisdom-based marketing strategies. Participants demonstrated positive changes in homestay management, including the use of more structured service standards and more creative promotions. Conclusion: The local wisdom-based management training proved effective in improving the capacity of homestay managers in Leuwimalang Tourism Village. This program contributes to strengthening the competitiveness of tourism villages and provides a model for community empowerment that can be replicated in other areas with similar characteristics. Limitations: This community service training was limited to a single location and used a short-term training approach. Contribution: This community service activity provides a practical contribution to strengthening the capacity of community-based tourism human resources and offers an adaptive training model that is relevant to the development of tourism villages, particularly in the context of vocational education and community empowerment based on local wisdom.